PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS PENDEKATAN KONTEKSTUAL DENGAN MATERI HUBUNGAN ANTAR KOMPONEN EKOSISTEM DAN JARING-JARING MAKANAN DI LINGKUNGAN SEKITAR - Afriantoni Suherja; Endang Widi Winarni; Irwan Koto (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2022)
This study aimed to describe (1) the characteristics of science teaching materials based on a contextual approach to ecosystem materials; (2) the feasibility of science teaching materials based on a contextual approach to ecosystem materials; (3) the responses of teachers and students to science teaching materials based on a contextual approach for teachers and students. The research method used was the Research and Development (R&D) method. Research instruments in interview guidelines, validation sheets, and chek- list response sheets. Six validators participated in invalidating content validity, graphical validity, and language validity. The data were analyzed using the Aiken V and Inter-rater reliability. The results of the study carried out content validation (0.89) with very valid criteria, presentation validation (0.94) very valid criteria, graphic validation (0.89) very valid criteria, and linguistic validation (0.90) very valid criteria. This study concludes that digital teaching materials based on a contextual approach are appropriate for SD Negeri 14 Kaur.